THE EFFECT OF USING AN ELECTRONIC TEXTBOOK IN HIGHER EDUCATIONAL INSTITUTIONS IN LABORATORY LESSONS IN CHEMISTRY - Nurutdinova Feruza (Новости образования: исследование в XXI веке, 2023)
Today, at the main stage of reforming education, it is very important to create a new generation of educational literature that meets the requirements of modernity. In our time, new modern information technologies open up a lot of opportunities. For example, computer, printer, scanner, multiplication, animation presentation and so on. This, in turn, simplifies the creation of an active learning system and e-books. As a result, it is possible to organize modern informative lectures, practical and experimental laboratories.